The Ca2+-CaM Signaling Pathway Mediates Potassium Uptake by Regulating Reactive Oxygen Species Homeostasis in Tobacco Roots Under Low-K+ Stress - Wang, Yingfeng; Dai, Xiaoyan; Xu, Gaoqiang; Dai, Zhuoyi; Chen, Peiyu; Zhang, Tongjin; Zhang, Huifen (Frontiers in Plant Science, 2021)
Potassium (K+) deficiency severely threatens crop growth and productivity. Calcium (Ca2+) signaling and its sensors play a central role in the response to low-K+ stress. Calmodulin (CaM) is a important Ca2+ sensor. However, the mechanism by which Ca2+ signaling and CaM mediate the response of roots to low-K+ stress remains unclear. In this study, we found that the K+ concentration significantly decreased in both shoots and roots treated with Ca2+ channel blockers, a Ca2+ chelator, and CaM antagonists. Under low-K+ stress, reactive oxygen species (ROS) accumulated, and the activity of antioxidant enzymes, NAKD, and NADPase decreased. This indicates that antioxidant enzymes, NADK, and NADPase might be downstream target proteins in the Ca2+-CaM signaling pathway, which facilitates K+ uptake in plant roots by mediating ROS homeostasis under low-K+ stress. Moreover, the expression of NtCNGC3, NtCNGC10, K+ channel genes, and transporter genes was significantly down-regulated in blocker-treated, chelator-treated, and antagonist-treated plant roots in the low K+ treatment, suggesting that the Ca2+-CaM signaling pathway may mediate K+ uptake by regulating the expression of these genes. Overall, this study shows that the Ca2+-CaM signaling pathway promotes K+ absorption by regulating ROS homeostasis and the expression K+ uptake-related genes in plant roots under low-K+ stress.